Implementation of Cloud Point Extraction Using Surfactants in the Recovery of Polyphenols from Apricot Cannery Waste - Ioannis Giovanoudis; Vassilis Athanasiadis; Theodoros Chatzimitakos; Dimitrios Kalompatsios; Eleni Bozinou; Olga Gortzi; George D. Nanos; Stavros I. Lalas (Eng, 2023)
The objective of this study was to investigate the feasibility of using Cloud Point Extraction (CPE) to isolate natural antioxidants (polyphenols) from apricot cannery waste (ACW). Four different food-grade surfactants (Genapol X-080, PEG 8000, Tween 80, and Lecithin) were tested at varying concentrations to evaluate the effectiveness of the technique. It was observed that low concentrations of surfactants in one-step CPE resulted in less than 65% polyphenol recovery, which necessitated further extraction steps. However, high concentrations of surfactants were found to significantly improve polyphenol extraction from ACW for all surfactants tested. Among the four surfactants, PEG 8000 was found to be the most effective in most circumstances; specifically, adding only 2% of the surfactant per step in a two-step CPE was enough to effectively extract polyphenols with recovery rates better than 99%. When 10% w/v of PEG 8000 was used, recoveries greater than 92% were obtained. Since PEG 8000 is a reagent with low toxicity and the CPE method is simple, rapid, cheap, sensitive, and selective, the extracted organic compounds from ACW can be used as natural antioxidants in food technology. This has important implications for the development of natural and sustainable food additives.